A Taxonomic Checklist of Insect Biodiversity in Loyola College Campus, Chennai, Tamil Nadu, India - Abirami , K; Balachander, M; Suresh M; Jothinathan, Mukesh Kumar Dharmalingam; Babu , N. Aravindha; Saravanan, Saantosh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Biodiversity, which refers to the entire array of life forms, genes, and ecosystems, was born as a result of the outcome of billions and billions of years of evolutionary development. In contrast to that, increasing the number of people and economy will impact biodiversity in the global level as it will not only destroy the ecosystems but also make them vulnerable to disruption. Preservation of biodiversity is undoubtedly one of the fundamental aspects that is necessary to keep species and genetic variations along with ecosystems. There is a large variety of insect species (more than half of all known life) and they are crucial for ecosystem functioning via pollination, nutrient recycling, and food web maintenance; However, they also act as vectors of diseases and pests. This research is focused on the insect diversity in Loyola College located in Chennai which was done through the Area Search Survey Method. Using a smartphone camera, the insects were imaged and then identified via iNaturalist. The reported data confirm the occurrence of various beetle classes, among which Lepidoptera is noted as the top order. The discussion delves into the ecological significance as well as economic influence of different insect groups which include services that they provide by way of pollination, pest control and so on. Awareness of insect biodiversity is important because of its role in ecosystem balance, agricultural stability, and human wellness.